Preimplantation Genetic Screening: An Effective Testing for Infertile and Repeated Miscarriage Patients? - Ning Wang; Ying-Ming Zheng; Lei Li; Fan Jin (Obstetrics and Gynecology International)
Aneuploidy in pregnancy is known to increase with advanced maternal age (AMA) and associate with repeated implantation failure (RIF), and repeated miscarriage (RM). Preimplantation genetic screening (PGS) has been introduced into clinical practice, screening, and eliminating aneuploidy embryos, which can improve the chance of conceptions for infertility cases with poor prognosis. These patients are a good target group to assess the possible benefit of aneuploidy screening. Although practiced widely throughout the world, there still exist some doubts about the efficacy of this technique. Recent randomized trials were not as desirable as we expected, suggesting that PGS needs to be reconsidered. The aim of this review is to discuss the efficacy of PGS.